Child development at 6 years after maternal cancer diagnosis and treatment during pregnancy. (1st November 2019) - Maggen, C; Van Calsteren, K; Cardonick, E; Shmakov, RG; Gziri, MM; Cabrera Garcia, A; Fruscio, R; Lok, CAR; Halaska, MJ; Boere, IA; Zola, P; Ottevanger, PB; et al.
Abstract : Introduction/Background: The International Network of Cancer, Infertility and Pregnancy was launched in order to register women of reproductive age with a cancer diagnosis. Over the years, the project has expanded with currently 2653 cases registered by 114 centres and an annual registration rate of 150 patients. The expected rising numbers of cancer diagnosis during pregnancy as a result of an increased age at first childbirth and the possibility of early cancer detection by the non-invasive prenatal testing calls for an ongoing evaluation of clinical practice. Moreover, women might become pregnant while exposed to new target therapies that are being introduced into oncological practice. Methodology: The INCIP database consists of a secured on-line registration tool. Oncological, obstetric and neonatal data are registered by members. Annual scientific meetings give updates on the ongoing research projects. Results: Most patients were registered in Belgium, the Netherlands, Italy and USA and one third of participating centres are non-European. Currently 2059 patients with a cancer diagnosis or treatment during pregnancy are registered, 395 women that received fertility preservation and 199 patients with a postnatal cancer diagnosis (figure 1 ). Breast cancer, lymphoma and cervical cancer are the most frequent registered cancer types and the majority of patients (67%) received antenatal cancer treatment (figure 2 ). Most women delivered a live born baby (88%), however 47% delivered preterm and 80% of preterm deliveries were medically induced. One-fifth of neonates (21%) were small for gestational age. Congenital malformations were reported in 3% of live births. Conclusion: Cancer occurring in women endangers obstetrical and neonatal outcome and potentially future fertility. The INCIP registry is open for further collection of data since for such a relatively rare situation, only a large scale project will provide better insights on maternal and foetal risks assessment, which is essential for optimal patient counselling and care. Disclosure: The INCIP network would not be able to operate without the ongoing support of ESGO. Furthermore the project is supported by the Research Foundation—Flanders (FWO) in Belgium (grant no G070514N) and the European Union's Horizon 2020 research and innovation program under grant agreement No 647047. There are no conflicting interests to declare.